What should we expect from innovation? A model-based assessment of the environmental and mitigation cost implications of climate-related R&D - Valentina Bosetti; Carlo Carraro; Romain Duval; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper addresses two basic issues related to technological innovation and climate stabilisation objectives: i) Can innovation policies be effective in stabilising greenhouse gas concentrations? ii) To what extent can innovation policies complement carbon pricing (taxes or permit trading) and improve the economic efficiency of a mitigation policy package? To answer these questions, we use an integrated assessment model with multiple externalities and an endogenous representation of technical progress in the energy sector. We evaluate a range of innovation policies, both as a stand-alone instrument and in combination with other mitigation policies. Even under fairly optimistic assumptions about the funding available for, and the returns to R&D, our analysis indicates that innovation policies alone are unlikely to stabilise global concentration and temperature. The efficiency gains of combining innovation and carbon pricing policies are found to reach about 10% for a stabilisation target of 535 ppm CO2eq. However, such gains are reduced when more plausible (sub-optimal) global innovation policy arrangements are considered.
Keywords: H0; H2; H3; H4; O3; Q32; Q43; Q54; 330; Climate Change; Environmental Policy; Energy R&D Fund; Stabilisation Costs